Justicia juvenil restaurativa: tendencias actuales y su impacto en la sociedad (Tema Central) - Calle Tapia, Milton Daniel (2023)
Historically, managing adolescent offenders has been a challenging task. Therefore, this academic article aims to expose how Restorative Juvenile Justice has become a valuable alternative to address this issue. An analysis of international concepts and practices related to this approach was conducted. The importance of this perspective in fostering personal responsibility and empowerment among adolescent offenders is emphasized, as well as in reducing recidivism and improving reintegration and repair for victims. Finally, the effectiveness of Restorative Juvenile Justice is emphasized as a more comprehensive option to address challenges in the juvenile justice system.